Design and Fabrication of Meat Shredder Machine Using VDI2221 Approach - Muchamad Oktaviandri; Ng Siew Kian (Faculty of Engineering and Technology, Sampoerna University, 2021)
Shredded meat is more palatable to the taste of consumer and preparing shredded meat in a large scale requires the aid of meat shredder machine. This paper presents a detailed design procedure of a meat shredder machine developed by the VDI2221 approach. This paper also elaborates on the design of each part of the machine which includes selecting the components of the cutting and transmission system, kinematic arrangement of forces, material selection on the machine and proportion of parts to ensure the maximum strength and functionality of the machine. Further, the design of the various parts of the machine in 3D model and machine fabrication are discussed, along with the testing on the function and geometric aspects to ensure the efficiency of the machine. This study developed a meat shredder machine with 0.5 Hp electric motor and capacity of 2 kg per hour.